Influence of the use of various imaging units and projections on the radiation dose received by children during chest digital radiography. - Hongrong Xu; Kaiping Huang; Bo Liu; Jinhua Cai; Huan Zheng; Helin Zheng; Qiurui Yang; Changhong Yao (PLoS ONE)
Objective To investigate the impact of the use of different imaging units and projections on radiation dose and image quality during chest digital radiography (DR) in 3- and 4-year-old children. Methods Two hundred forty 3- and 4-year-old participants requiring chest DR were included; they were divided into three groups: supine anterior-posterior projection (APP), standing APP and standing posterior-anterior projection (PAP). Each group included 40 participants who were evaluated using the same imaging unit. The dose area product (DAP) and the entrance surface dose (ESD) were recorded after each exposure. The visual grading analysis score (VGAS) was used to evaluate image quality, and the longitudinal distance (LD) from the apex of the right lung to the apex of the right diaphragm was used to evaluate the inspiration extent. Results DAP and ESD were significantly lower in the standing PAP and APP groups than in the supine APP group (P<0.05), but LD was significantly higher in the standing PAP and APP groups than in the supine APP group (P<0.05). Additionally, the pulmonary field area was significantly higher for the standing PAP group than for the standing and supine APP groups (P<0.05). The correlations between ESD, DAP, and VGAS were positive (P<0.001), showing that larger ESD and DAP correspond to higher VGAS. The correlations between ESD, DAP, and body mass index (BMI) were also positive (P<0.05), indicating that higher BMI corresponds to larger ESD and DAP. Finally, no differences in DAP, ESD, VGAS, LD, pulmonary field area, or BMI were noted between males and females (P>0.05). Conclusion The radiation dose to superficial organs may be lower with standing PAP than with standing APP during chest DR. Standing PAP should be selected for chest DR in 3- and 4-year-old children, as it may decrease the required radiation dose.